Dakwah Strategy of YukNgaji Community Towards Hallyu Fans through Korean Nuanced Content - Mutiarani, Afifi; Mufidah, Ghina; Yusuf, Maulana (UIN Antasari Banjarmasin, 2024)
The Korean-themed content produced by the YukNgaji community represents an innovative approach to da'wah in response to global trends. This study aims to analyze YukNgaji community's da'wah strategies targeting